An Investigation into what factors influence the expectation of life made by life insurance companies. - Anand, Aniel (2006)
The increasing life expectancy trend that is observed at present means that pensioners are increasingly facing the problem of longevity risk (the risk of living longer than one can financially sustain themselves). As a result, there is an increasing demand for annuities, so that the longevity risk can be transferred from the annuitant to the insurer.